PEMBUATAN KOMPOS DARI KOTORAN SAPI DENGAN BAHAN CAMPURAN KALAKAI DI KELOMPOK TERNAK NGUDI MAKMUR DI KALAMPANGAN - paulini, paulini paulini (Buletin Udayana Mengabdi, 2020)
ABSTRACT             Kalampangan Village is located in Sebangau Subdistrict, Palangka Raya City, constituting 80% of vegetable commodity producers for the needs of Palanagka RayaCity residents.  In addition to being farmers, some of the Kalampangan residents also have raising cattle.  The total area of Kalampangan village is 46,25 m 2 (5.000 hectares), consisting of 5 neighborhoods and 27 neighboring neighborhoods with a population of 3,183 inhabitants, consisting of 1,559 male and 1,558 female.  The people in Kalampangan are mainly engaged in vegetables gardening, with planting areafor vegetables reaching 400 hectares and harvested area of around 380 hectares.  In addition in their agricultural activities, residents in Kalampangan also raise cattle.  Thus make Kalampangan as one of the suppliers of beef in Palangka Raya City.  This community service activity aimed to help solve farmers’ problems by turning cow dung into compost with simple technology in a composthouse.  This activity is carried out in several stages.  First stage of this activity was provide counseling for farmers about the dangers of piles of cowdung around the environment of cattle pen and the use of it        into compost that can be a business opportunity for farmers.  The next stage was practice of making compost mixed with kelakai which is known as peat weed. Key words:  Cow Dung, Compost, Kelakai